Animal shenanigans : twenty-four creative, interactive story programs for preschoolers - Reid, Rob, 1955- (ALA Editions, an imprint of the American Library Association, 2015)
Animals have been a staple in children's books for decades. Reid has created story program lesson plans featuring our four-legged, no-legged, winged, scales, and feathered friends. You and your group will have a howling, barking, clucking, roaring good time!--